High Internal Phase Pickering Emulsion Stabilized by Natural Biomacromolecules and Its Application in Foods - WEI Kongju, DONG Tongjun, ZHU Guohua, SHUANG Yuan, XIAO Shensheng, WANG Xuedong, DING Beibei (Shipin Kexue, 2023)
In recent years, high internal phase Pickering emulsions (HIPPEs) has attracted much attention due to its unique organizational properties and has a wide application prospect in the food field. Natural biomacromolecules, active components in organisms, possess good biocompatibility, degradability, no or low toxic effects, which are excellent stabilizers for HIPPEs. In this paper, the potential of natural biomacromolecules to stabilize HIPPEs and recent progress on the application of biopolymer-stabilized HIPPEs in the inhibition of lipid oxidation, as a substitute for trans fatty acids, and in the encapsulation and delivery of nutrients, the 3D printing of foods and encapsulation of probiotics are briefly reviewed in order to provide a reference for the application of HIPPEs stabilized by natural biomacromolecules in foods.